The Effect Of Administration Of Acupressure Li4 (Hegu) On The Scale Of Labor Pain In Active Phase 1 In Primipara Mothers In Sehati Kepanjen Maternity Homes - Mustika Dewi; Novida Ariani; Anjar Diasti Amna (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether there is an effect of giving LI4 (hegu) acupressure on pain during labor in primiparous mothers in RB Sehati Kepanjen. This study uses the True Eskperimen method (pure experiment) in the form of a post test only control design. The sample used in this study were mothers who were about to give birth entering an opening of 4-10 cm as many as 33 mothers gave birth at the Sehati Kepanjen Maternity Home, where the sampling technique was simple random sampling. The LI4 (Hegu) acupressure method is located in the middle of the first and second metacarpals by applying gentle pressure to the protruding area during labor pain. The scale for measuring labor pain in this study was the Wong-Baker Cat FACES Rating Scale. Data analysis used independent t-test statistical test because the data were normally distributed. The results showed that there was an effect of giving acupressure LI4 (Hegu) on the intensity/scale of maternal pain, especially in the first period at RB Sehati Kepanjen, with T count = 8,383 sig = 0.0001 < 0.05, which means there is a difference in pain where the control group higher (8.59) than the treatment (3.75) statistically stated that there was a significant difference, there was a difference between the control group and the treatment group. The control group (without acupressure LI4) was higher than the treatment group (which was given acupressure LI4).